CHALLENGES OF INTELLECTUAL PROPERTY RIGHT PROTECTION IN THE OUTER SPACE - Oluwajobi, Yewande Fadeke; Adedeji, Adewole A. (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
As more private entities get involved in space activities, the issue of intellectual property would continue to dominate the conversation because the international laws on space activities appeared to ban property rights in outer space. Juxtaposing the exclusionary nature of protection for intellectual property rights on earth with the terrestrial nature of outer space activities is challenging, yet states and companies have to deal with the challenge. This study examined the challenges of protecting intellectual property rights in outer space in relation to private sectors’ activities. The study employed the doctrinal method of research with emphasis on the international customary laws on outer space. The study found that international customary laws did not address protection of intellectual property rights in outer space, and that dispute settlement mechanisms for addressing the issues were not inadequate. The study concluded with an appraisal of Nigeria’s activities in space and the need to improve on their visibility in the global space.